2016
DOI: 10.1007/s00705-016-2997-2
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic patterns of circulating influenza virus from 2005 to 2012 in Shandong Province, China

Abstract: To identify circulating emerging/reemerging viral strains and epidemiological trends, an influenza sentinel surveillance network was established in Shandong Province, China, in 2005. Nasal and/or throat swabs from patients with influenza-like-illness were collected at sentinel hospitals. Influenza viruses were detected by reverse transcription polymerase chain reaction (RT-PCR) or virus isolation. From October 2005 to March 2012, 7763 (21.44 %) of 36,209 swab samples were positive for influenza viruses, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Virological data of influenza virus demonstrated that an annual cycle with one peak in winter was noticeable in the temperate region of China, including Beijing and Shandong province [27, 28]. Influenza virus peaked in summer in Guangdong province in subtropical southern China [29]. However, seasonal pattern was not determined in Chongqing which is adjacent to Sichuan province [30].…”
Section: Discussionmentioning
confidence: 99%
“…Virological data of influenza virus demonstrated that an annual cycle with one peak in winter was noticeable in the temperate region of China, including Beijing and Shandong province [27, 28]. Influenza virus peaked in summer in Guangdong province in subtropical southern China [29]. However, seasonal pattern was not determined in Chongqing which is adjacent to Sichuan province [30].…”
Section: Discussionmentioning
confidence: 99%
“…The seasonal patterns of ILI and circulating strains in Shenyang were similar to those of other regions in northern China [27][28][29]; however, the virological characteristics of influenza virus differed from those in southern China where an annual cycle with two peaks in summer and winter was pervasive [18,30]. This discrepancy may be due to climate or meteorological factors.…”
Section: Discussionmentioning
confidence: 73%